1973
DOI: 10.1159/000251868
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pemphigus and Pemphigoid with Azathioprine

Abstract: The results obtained with azathioprine in 10 patients with pemphigus and pemphigoid are reported. Seven of these patients showed a very good response to azathioprine alone. In two patients an initial high dosage of corticosteroids could be considerably reduced after azathioprine was added. In one patient a short initial azathioprine treatment gave noimprovement. Further investigations on the clinical usefulness of this drug are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…As a basis for this study, a small number of previous reports describing AZP monotherapy to treat autoimmune bullous diseases were uncovered ( Table 2). [10][11][12][13] These reports suggested that AZP monotherapy had a positive effect on the patients (between two and eight cases) in each study, and most were successfully treated using AZP alone during the early stages of the disease, implying that the lesions were not extensive or spreading rapidly. 12 Our results demonstrate that seven out of 10 cases were controlled using AZP monotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…As a basis for this study, a small number of previous reports describing AZP monotherapy to treat autoimmune bullous diseases were uncovered ( Table 2). [10][11][12][13] These reports suggested that AZP monotherapy had a positive effect on the patients (between two and eight cases) in each study, and most were successfully treated using AZP alone during the early stages of the disease, implying that the lesions were not extensive or spreading rapidly. 12 Our results demonstrate that seven out of 10 cases were controlled using AZP monotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…In three cases, azathioprine was successfully used as a monotherapy to induce and maintain clinical remission with a fall in antibody titre 30,34 . However, there is a latent period of at least 6 weeks before the effects of azathioprine are seen 29–31,34 and its use as monotherapy to induce remission should be reserved for mild cases only.…”
Section: Azathioprinementioning
confidence: 99%
“…In the four institutions where patients were treated only with corticosteroids during these two periods of time, mortality de¬ creased by 48% to 84% in all institutions within a span of 10 to 20 years.110"15 Thus, improvement in survival during those years must, in whole or in part, be due to factors other than the introduction of adjuvant therapies, such as a diagnosis of a mild form of the disease, earlier initiation of therapy, and better treatment of complications.1 66 (20.5) 64(28.1) 35 (30) 12 (57) 13 (45) 25 (32) Unfortunately, there has been no further reduction in mortality during the past decade (average, 6.2%; range, 0% to 10%). Mortality continued to decline rap¬ idly in the 1960s and 1970s, to an average of 5.9%, coincident with the introduction of adjuvant therapy with immunosuppressive drugs.…”
mentioning
confidence: 99%